Leflunomide Inhibits Proliferation and Induces Apoptosis via Suppressing Autophagy and PI3K/Akt Signaling Pathway in Human Bladder Cancer Cells - Cheng L; Wang H; Wang Z; Huang H; Zhuo D; Lin J (Dove Medical Press, 2020)
Li Cheng,1,* Hao Wang,2,* Zicheng Wang,3 Houbao Huang,1 Dong Zhuo,1 Jian Lin4 1Department of Urology, The First Affiliated Hospital, Yijishan Hospital of Wannan Medical College, Wuhu, Anhui Province, People’s Republic of China; 2Department of Geriatrics, Peking University First Hospital, Beijing, People’s Republic of China; 3Department of Urology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui Province, People’s Republic of China; 4Department of Urology, Peking University First Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Cheng Email chenglibjmu@163.comIntroduction: Bladder cancer is a lethal human malignancy. Currently, treatment for bladder cancer is limited. The anti-tumor effects of leflunomide have attracted much more concern in multiple human cancers.Materials and Methods: This study evaluated the anti-tumor effects of leflunomide on cell viability, colony formation, apoptosis, and cell cycle in two human bladder carcinoma cell lines, 5637 and T24. Meanwhile, the underlying mechanism including PI3K/Akt signaling pathway and autophagy modulation was also identified.Results: Leflunomide markedly inhibited the growth of both bladder cancer cell lines and induced apoptosis and cell cycle arrest in S phase. The phosphorylation levels of Akt and P70S6K in both cell lines were significantly down-regulated with leflunomide treatment. Furthermore, the deceased formation of autophagosomes and the accumulation of LC3II and P62 suggested the blockade of autophagy by leflunomide. Modulation of autophagy with rapamycin and chloroquine markedly attenuated and enhanced the cytostatic effects of leflunomide, respectively.Conclusion: Leflunomide significantly reduced the cell viability of bladder cancer cells via inducing apoptosis and cell cycle arrest and suppressing the PI3K/Akt signaling pathway. In addition, the blockade of autophagy was observed, and autophagy inhibition enhanced leflunomide-mediating anti-tumor effects. Our data presented here offer novel ideas for comprehensive therapeutic regimes on bladder cancer.Keywords: leflunomide, autophagy, PI3K/Akt pathway, anti-tumor, bladder cancer